Staining Capability of Plant Extracts for the Identification of Gram-positive and Gram-negative Bacteria: A Systematic Review - Badar, Rae Antoinette D.; Carmona, Junissa Lalaine R.; Collantes, John Gabriel C.; Lojo, Daneery R.; Ocampo, Sean Mairose B.; Ursua, Roxette Lorie C.; Bercede, Daniel H. (Asian Journal of Biological and Life Sciences)
Background: Gram Staining is an essential diagnostic procedure where bacteria are stained to be properly identified. However, the stains used were found to be toxic with carcinogenic properties and (insert may) potentially harm living organisms as well as the environment.Methods:To address this issue, plant extracts were utilized in different experiments to test their staining capability on the bacteria. This study provides a systematic review of online articles and studies related to the staining capabilities of various plants.Results: Following the inclusion and exclusion criteria, a total of 137 papers were reviewed and only 11 papers were included in the study. Both the presence of phytochemicals and the pH concentration influenced the staining capacity of most plant extracts. In the following studies that were examined, most of the plants were able to stain gram-positive bacteria in comparison to the gram-negative bacteria.Conclusion: It was found that oxidized aqueous (hot or cold) extract ofLawsonia inamis, methanolic extracts ofSolanum melongenaL., 100% concentration of ethanolic extracts of Ipomoea batatas, ethanolic extract ofClitoria ternatea,Pterocarpus osunextracts,Bixa orellanaextracts, andHibuscus sabderiffaextract were able to stain the bacteria. Meanwhile, certain extracts have poor staining capability namely Garcinia kola mesocarp,Vitex donianafruit,Lantana aculaetafruit,Cnestis ferrugneafruit, andPterocarpus soyauxiistem. It is recommended to find other alternative extracts along with various extraction methods and concentration levels that may further enhance the affinity of the stain.
Keywords: Dyes; Gram-negative bacteria; Gram-positive bacteria; Plant Extracts; Stain